Design, development and analysis of a haptic-enabled modular flexure-based manipulator. (December 2016) - Pinskier, Joshua; Shirinzadeh, Bijan; Clark, Leon; Qin, Yanding; Fatikow, Sergej
Abstract: The development of many applications of microtechnology requires flexible new manipulation tools to perform micromanipulation tasks. A modular piezo-actuated translational flexure-based mechanism is investigated as a basis for the construction of bespoke micromanipulators. The design allows individual single degree of freedom (DOF) translational modules to be serially coupled to form manipulators with multiple DOFs. When the resulting system is controlled through a teleoperated haptic control scheme, it enables a human operator to intuitively perform a broad range of micromanipulation tasks. The mechanical design of the modular system and the haptic control architecture is presented in this paper. Computational analysis is conducted to verify the design methodology, and a planar 2-DOF manipulator experimentally studied to validate the modular concept. Utilizing the 2-DOF system, the haptic control scheme is demonstrated to accurately track user motions, and guide task performance.